Exploring the agenda-setting potential of homeland online newspapers on perceptions of elections issues among diasporic Nigerians in Malaysia - Mustapha, Lambe Kayode; Wok, Saodah (IIUM Press, 2015)
The increasing transnational migration of people and availability of homeland newspapers on the web have stimulated interest in the understanding of the use and effects of homeland media on a nation’s foreign residents. This study explores the relationship between the agenda covered in three Nigerian online newspapers (N=260) and how they were perceived by Nigerian students in Malaysia (N=350) during the 2011 Nigerian presidential election. Specifically, the issues in online newspapers and their location (homepage and index) and length were compared with the issues perceived as being important by Nigerian students in Malaysia. Comparing content analysis data with survey responses, the findings revealed a modest but plausible support for the agenda-setting potential of the online newspapers. In view of the established correspondence between issues that are salient in the news and issues perceived by the readers, the study establishes the importance of homeland online media to political cognitions and actions among diasporic Nigerians. It also suggests the need to explore other cues in the online newspapers capable of raising the salience of issues in the perceptions of the Nigerian diaspora.